Negative and positive synergies: On employee development practices, motivational climate, and employee outcomes - Nerstad, Christina G.L.; Dysvik, Anders; Kuvaas, Bård; Buch, Robert (Human Resource Management, 2018)
While previous studies have increased our knowledge of how employees’ perceptions of development practices influence employee outcomes, the role of potential contingencies in this relationship remains relatively unexplored. In the present study, we set out to contribute to this research by exploring whether congruence or lack of congruence between perceived employee development practices and the perceived motivational climate at work influence employee performance and turnover intention. A field study among 169 employees from a Norwegian financial organization revealed that lack of congruence may be detrimental in terms of work performance and turnover intention. Implications for practice and future research are discussed.